IDENTIFICATION OF BURIED ARCHEOLOGICAL OBJECTS WITH RADIAL DERIVATIVES OF MICRO GRAVITY DATA - Zuhdi, Muhammad; Sukrisna, Bakti; Syamsuddin, Syamsuddin (Universitas Mataram, 2019)
The development of recent gravimetric technology allows us to measure gravity anomalies with accuracy of micro Gal. Micro gravity is able to detect very small gravity anomalies such as anomaly due to buried archeological objects below the earth surface. Radial Derivatives of gravity data is used to sharpen anomaly due to lateral changes of density contrast. Horizontal derivatives carried out by previous researchers have some weaknesses, i.e. the loss of derivative values in certain directions and inconsistence values at the source boundary of the same anomaly edge. To solve the horizontal derivative problem, a radial derivative is made. Radial derivative is derivative of gravity anomaly over horizontal distance in the radial direction from a certain point which is considered as the center of anomaly. There are two kind of radial derivative i.e. First Radial Derivative (FRD) and Second Radial Derivative (SRD). Blade Pattern is another way to enrich the ability of SRD to detect boundary of anomaly source. Synthetic gravity data of buried archeological object was made by counting the response of forward modelling. All of programs and calculation of the models in this research is performed based on MatlabÂ® program. The results of the tests on the synthetic data of the model show that the radial derivative is able to detect the boundaries in buried temples due to density contrast. The advantage of radial derivatives which is a horizontal derivative in the direction of radial compared to ordinary horizontal derivatives is the ability to detect vertical boundaries of various anomaly due to horizontal layers and capable of showing density contrast in almost all directions.